Performance of Cultivars for Production of Green Corn in Different Planting Dates in Passos Region, MG - Vargas, P. F. [UNESP]; Andrade, M. A. P. [UNESP] (Int Soc Horticultural Science, 2012)
The aim of this work was evaluating the performance of several cultivars of green corn for consumption 'in natura' in different planting dates. The first planting date was on May 26th, and the others, every 40 days. The hybrids (treatments) were: AG-1051, Agroeste 1567, BM-3061, Prezoto-32D10, PL-6880, BX-1382 and GNZ-2004. The following characteristics were evaluated: production, commercial ears weight without husk, commercial ears number, commercial ears diameter and length, male flowering, plant height and height of ear corn insertion. The cultivars AG1051, Agroeste 1567 and BM 3061 presented the best results compared to the others and they should be used in green corn production for ` in natura' consumption in Passos County, MG.
Keywords: 'in natura' consumption; hybrids; Zea mays L.